THE IMPORTANCE OF COMMUNICATIVE APPROACH IN TEACHING PROFESSION-ORIENTED ENGLISH AT TECHNICAL COLLEGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In modern technical education, the role of English language teaching has significantly expanded beyond basic grammar and vocabulary instruction. Technical college students are required to develop communicative competence that enables them to use English effectively in professional and occupational contexts. This article examines the importance of the communicative approach in teaching professionoriented English at technical colleges.